Perancangan Aplikasi Pengelolaan Surat pada Dinas Kependudukan Catatan Sipil Kabupaten Aceh Besar - Munawir Munawir; Susmanto Susmanto; Zulfan Zulfan; Taufik Hidayat (Fakultas Teknik, 2020)
Currently, technological development is very much needed as information systems are increasingly stringent and require the readiness of an organization. Government agencies very much manage and serve the community so that the role of government is very influential to serve the community for example for the management of correspondence. The use of the existing mail information system does not meet the standards of technological development, because the existing data processing system is still done manually using Microsoft Word. The problem that is often faced when making a letter by hand is that people who make a letter have to wait a long time, because officers must input data manually. The purpose of this research is to create a system to serve the public in making letters, so that officers can provide services quickly and accurately. The results of this study are the information system that was designed to be able to provide convenience and update the administration of the letter agenda that previously was still using the manual method.